Warriors : SkyClan & the stranger - Hunter, Erin; Jolley, Dan (Hunter, Erin. Warriors (Graphic novel), 2019)
"Newleaf is coming, and Leafstar is proud to see SkyClan thriving under her leadership. But when the arrival of a mysterious stranger throws SkyClan into turmoil, Leafstar must figure out what is best for her Clan--once and for all. With newly colorized art, this stand-alone manga adventure is perfect for the collections of longtime Warriors readers or any graphic novel fan."--Provided by publisher